Applying market shaping approaches to increase access to assistive technology in low- and middle-income countries. (1st December 2021) - Savage, Margaret; Albala, Sarah; Seghers, Frederic; Kattel, Rainer; Liao, Cynthia; Chaudron, Mathilde; Afdhila, Novia
ABSTRACT: Development outcomes are inextricably linked to the health of the marketplace that delivers products and services to people in low- and middle-income countries (LMIC). Shortcomings in the market for assistive technology (AT) contribute to low access in LMIC. Market shaping is aimed at improving a market's specific outcomes, such as access to high quality, affordable AT, by targeting the root causes of these shortcomings. The paper summarizes the findings of market analyses conducted under the UK aid funded AT2030 programme in support of ATscale and aims to discuss how market shaping can help more people gain access to the AT that they need and what are the best mechanisms to unlock markets and commercial opportunity in LMICs. The paper also explores how market shaping for AT markets could be part of a mission-oriented approach AT policy. A mission-oriented approach can help accelerate progress toward a common objective among stakeholders, at country or global level. While market-shaping activities direct the outcomes of the market toward a specific end goal, such as access to quality, affordable products and services, missions are more comprehensive and include other policy interventions and stakeholder collaborations in order to create a robust and sustainable structure.